DVC DIGITAL VIDEO COMMERCIAL OF PAKISTANI FOOD ADVERTISING INDUSTRY: A QUALITATIVE ANALYSIS OF CONTEMPORARY DIGITAL TRENDS IN ADVERTISING INDUSTRY (Contemporary Journal of Social Science Review, 2025)
After the Covid-19 pandemic, a rapid digital transformation in the advertising industry of Pakistan has also been observed. This research explores how Digital Video Commercial (DVC) are reaching out to a larger audience as compared to Television Video Commercial (TVC) audience through digital screens. The persuasive techniques and treatments and ideas presented in DVCs have been seen through the lens of narrative paradigm, employing a qualitative approach of content analysis of two DVCs launched after the emergence of pandemic. Sultan and Shan cooking oils brands were taken to explore the narrative discourse. Narrative paradigm that includes; Narration (story telling), Based on good reasons (narrative coherence), Fidelity of narration, technical aspects. Findings shows that DVCs seems to have more elaborative discourse by unfolding story, reasoning, fidelity and technical treatment.